The Role of Christian Educators Utilizing Social Media in the Learning Process for Students - Kainara, Semi Darius; Kotte, Yohanes; Mau, Marthen (Formosa Journal of Applied Sciences, 2024)
The presence of social media has a big influence on the general public, including students, to make it easier to carry out the learning process because they can get various information and data related to learning material, communication with fellow friends, for entertainment, and various other important information. The purpose of this research is to explain the role of Christian educators in making good use of social media for students so that social media can be used for greater interaction because of the ease of facilities in disseminating good information. The research method used is qualitative research with a library research approach. The results of this research are that if Christian educators care more about students in providing a correct understanding of the use of social media, then social media will be of great benefit in the learning process held both at school and doing assignments at home.